Melt flowing behaviors and microstructure evolution during laser offset welding of dissimilar metals between AH36 and 304 steels. (July 2022) - Liu, Fuyun; Zhou, Xiaohui; Chen, Xi; Gong, Xiangtao; Wu, Laijun; Chen, Bo; Chen, Kai; Tan, Caiwang
Highlights: Laser welding dissimilar steels with varying laser offset was studied. Different austenite/martensite phase balance was achieved by adjusting laser offset. Varying thermophysical properties in both steels led to asymmetrical fusion boundary. Inhomogeneous element distribution was obtained due to inadequate melt flow. Abstract: The study aimed to reveal the mechanism of microstructure evolution in the fusion zone of dissimilar AH36 and 304 steel laser welds and provide a feasible method for controlling austenite/martensite phase balance via adjusting laser offset (defined 304 side (-) and AH36 side (+)). The results suggested that asymmetrical fusion line boundaries were observed when centerline of dissimilar joints was irradiated by laser beam (L = 0 mm). Besides, fraction of austenite phase in weld center was decreased from 10.8% to 0.01% and broader inherited lathy martensite grain was obtained when laser offset shifted from 304 stainless steel side of 0.5 mm (L = −0.5 mm) to AH36 steel side of 0.5 mm (L = 0.5 mm). Microstructural difference of fusion zone under varying laser offset was determined by Gibbs free energy of the martensite transformation and growth time of matrix-austenite grain, which were related with element distribution and cooling rate from austenitic temperature to Ms temperature. The inhomogeneous element distribution was observed due to inadequate mixing of two liquid steels when L = −0.5 mm while strong mixing was obtained at L = 0 mm and L = 0.5 mm. The phenomenon was attributed to different dilution of base metal irradiated by laser beam and driving force for melt flowing. Therefore, more martensite grains resulted in increasing average hardness with laser offset shifting from −0.5 to 0.5 mm while impact absorbed energy was lower, due to weaker deformation capacity of coarse martensite grain.